Quality of life in patients with coronary heart disease: interrelation with components of metabolic syndrome and markers of systemic inflammation - I. D. Bespalova; V. V. Kalyuzhin; Yu. A. Medyantsev (Бюллетень сибирской медицины)
Study objective: study of the interrelation between the indicators of quality of life (QL) in patients with coronary heart disease and risk factors of this pathology united by the framework of metabolic syndrome (MS) and the degree of activity of systemic inflammatory response. 110 patients with coronary heart disease have been examined. Along with the complete clinical, laboratory and instrumental examination, adopted in a specialized cardiology clinic, the study of QL was carried out with the help of the MOS SF-36 questionnaire, and also the analysis of activity of systemic inflammatory response was performed. It was shown that in the cluster of MS components there is a reverse correlation interrelation with abdominal obesity, hypertension and hyperglycemia. Also, a reverse correlation interrelation between the indicators of QL and some non-specific inflammatory markers (erythrocyte sedimentation rate, the concentration of C-reactive protein in blood) was discovered.